EVALUASI HARGA OBAT DI APOTEK KOTA BENGKULU - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
Background: Drug is a special commodity, which is important for health and human safety, and remains the biggest component in health service cost structure in I ndonesia. In Indonesia drug prices are higher compared to other developing countries. With continuous economic crisis and the decreasing of public buy power, alternative choice in cheaper drug with the equal quality is needed. While pharmaceutical industry in Indonesia grows rapidly, there are various drugs quantities and types with various price at retailer level. The studies are necessary on these various price of drugs in order to collect alternative choices about them. Methods: This study was designed as non-experimental, cross sectional survey and descriptive study. Prescription data and price list was collected retrospectively at 28 pharmacies in Bengkulu. The study examined selling-price of 29 generics and their brand names which were prescribed widely. Comparison was made to the standard price list of generics which was issued by the National Agency for Food and Drug Control 2001 and the International Price Indicator Guide 2001. Result: The results showed that the selling-price listed of the generics of National Agency for Food and Drug Control was surprisingly 2,12 times higher than the International Drug Price Indicator Guide 2001. The average selling-price of brand names was around 1.45-7, 97 times higher to the International Guide, and that to generic products was around 0.75-1.33. The range of ratio indicated that there were a few brand names with lower selling-price than generics, including amoxicilline 500 mg, mefenamic acid 500 mg, thiamphenicol 500 mg, contrimoxazole 480 mg, ciprofloxacin 500 mg, dexamethasone 0,5 mg, rifampicin 450 mg, and pyrazinamide 500 mg. In the other hand, some generics were more expensive than their cheapest brands, such as paracetamol 500 mg, ambroxol HCI 30 mg, aminophilline 200 mg, combination of pyrimetamin 25 mg+sulfadoxine 500 mg, ranitidine 150 mg, captopril 25 mg and allopurinol 100 mg. Conclusion: From the description above, it can be concluded that the average selling-price of branded name 2-6 times higher than that of generics and the average selling-price of generics was higher than the International Price Indicator. Keywords: generics brand names, selling-price, pharmacies